2019
DOI: 10.1089/scd.2019.0142
|View full text |Cite
|
Sign up to set email alerts
|

Inducing Pluripotency in the Domestic Cat (Felis catus)

Abstract: Domestic cats suffer from a range of inherited genetic diseases, many of which display similarities with equivalent human conditions. Developing cellular models for these inherited diseases would enable drug discovery, benefiting feline health and welfare as well as enhancing the potential of cats as relevant animal models for translation to human medicine. Advances in our understanding of these diseases at the cellular level have come from the use of induced pluripotent stem cells (iPSCs). iPSCs are capable o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(34 citation statements)
references
References 57 publications
(69 reference statements)
1
27
0
Order By: Relevance
“…In comparison with canine cells, feline amniotic MSCs showed a much lower expression of Sox2 and less immunostaining of the protein compared to canine amniotic stem cells [39]. In addition, a number of labs have shown that induced pluripotent stem cells derived from feline fibroblasts express Sox2 [40,41]. However, the presence of Sox2 in feline adipose-derived MSCs is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…In comparison with canine cells, feline amniotic MSCs showed a much lower expression of Sox2 and less immunostaining of the protein compared to canine amniotic stem cells [39]. In addition, a number of labs have shown that induced pluripotent stem cells derived from feline fibroblasts express Sox2 [40,41]. However, the presence of Sox2 in feline adipose-derived MSCs is controversial.…”
Section: Discussionmentioning
confidence: 99%
“…Feline iPSCs have recently been reported for the first time by our group, the development of which represents a significant step in the generation of iPSC derived cardiomyocytes from a veterinary species (Dutton et al, 2019). It paves the way for generating further cell lines from feline patients carrying the HCM causing MYBPC3/R820W mutation to test novel therapeutics for modifying the disease.…”
Section: Human and Feline Hypertrophic Cardiomyopathymentioning
confidence: 99%
“…It is worth noting that only very recently, in 2019, the cat ( Felis silvestris catus ; Linnaeus, 1758) contributed to expand the list of companion animals used as source of iPSCs (fiPSCs), although already in 2012 Verma et al (2012, 2013) generated these cells from wild felines. In 2019, Dutton et al (2019) isolated feline fibroblasts from adipose tissue and transfected them via Moloney murine leukemia virus containing human KOSM along with Nanog used as ESC‐like marker. By testing different derivation conditions, they set‐up a protocol for feline iPSCs induction observing that these cells require fetal bovine serum and feline leukemia inhibitory factor (LIF) to be maintained in culture for more than 3–5 days (Dutton et al, 2019).…”
Section: Nonrodent Animal‐derived Ipsc For Biomedical Applicationsmentioning
confidence: 99%
“…In 2019, Dutton et al (2019) isolated feline fibroblasts from adipose tissue and transfected them via Moloney murine leukemia virus containing human KOSM along with Nanog used as ESC‐like marker. By testing different derivation conditions, they set‐up a protocol for feline iPSCs induction observing that these cells require fetal bovine serum and feline leukemia inhibitory factor (LIF) to be maintained in culture for more than 3–5 days (Dutton et al, 2019).…”
Section: Nonrodent Animal‐derived Ipsc For Biomedical Applicationsmentioning
confidence: 99%
See 1 more Smart Citation